Household use of polluting cooking fuels and late-life cognitive function: A harmonized analysis of India, Mexico, and China. (November 2021) - Saenz, Joseph L.; Adar, Sara D.; Zhang, Yuan S.; Wilkens, Jenny; Chattopadhyay, Aparajita; Lee, Jinkook; Wong, Rebeca
Highlights: Household pollution from polluting fuels remains common in India, Mexico, and China. Using polluting cooking fuels was associated with poorer cognition in each country. Polluting cooking fuel use effects were equivalent to an additional 3-6 years of age. Abstract: Introduction: Exposure to high levels of air pollution is associated with poor health, including worse cognitive function. Whereas many studies of cognition have assessed outdoor air pollution, we evaluate how exposure to air pollution from combustion of polluting household fuels relates with cognitive function using harmonized data from India, Mexico, and China. Materials & methods: We analyze adults age 50+ in three nationally representative studies of aging with common data collection methods: the 2017–2019 Longitudinal Aging Study in India (n = 50, 532), 2015 Mexican Health and Aging Study (n = 12, 883), and 2013 China Health and Retirement Longitudinal Study (n = 12, 913). Use of polluting fuels was assessed by self-report of wood, coal, kerosene, crop residue, or dung for cooking. Cognitive function was measured by performance across several cognitive domains and summarized into a total cognition score. We used linear regression, by country, to test how polluting cooking fuel use relates with cognition adjusting for key demographic and socioeconomic factors. Results: Approximately 47%, 12%, and 48% of respondents in India, Mexico, and China, respectively, relied primarily on polluting cooking fuel, which was more common in rural areas. Using polluting cooking fuels was consistently associated with poorer cognitive function in all countries, independent of demographic and socioeconomic characteristics. Adjusted differences in cognitive function between individuals using polluting and clean cooking fuel were equivalent to differences observed between individuals who were 3 years of age apart in Mexico and China and 6 years of age apart in India. Across countries, associations between polluting cooking fuel use and poorer cognition were larger for women. Conclusions: Results suggest that household air pollution from the use of polluting cooking fuel may play an important role in shaping cognitive outcomes of older adults in countries where reliance on polluting fuels for domestic energy needs still prevails. As these countries continue to age, public health efforts should seek to reduce reliance on these fuels.